2014
DOI: 10.1038/bjc.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre-diagnostic cigarette smoking on colorectal cancer survival: overall and by tumour molecular phenotype

Abstract: Background:Smoking is a risk factor for incident colorectal cancer (CRC); however, it is unclear about its influence on survival after CRC diagnosis.Methods:A cohort of 706 CRC patients diagnosed from 1999 to 2003 in Newfoundland and Labrador, Canada, was followed for mortality and recurrence until April 2010. Smoking and other relevant data were collected by questionnaire after cancer diagnosis, using a referent period of ‘2 years before diagnosis' to capture pre-diagnosis information. Molecular analyses of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 33 publications
11
65
2
Order By: Relevance
“…However, smoking was also positively associated with colorectal cancer-specific mortality, and the biologic mechanisms underlying this association are not well understood. 18, 38,39 Other mechanisms for the adverse impact of smoking on colorectal cancer-specific survival may include decreased efficacy of colorectal cancer treatment among smokers. [11][12][13] Although MSI-high tumors generally demonstrate higher survival, 33,34 BRAF mutation status is independently associated with higher risk of mortality, 35 and CIMP-high status in microsatellite-stable tumors is also associated with lower survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, smoking was also positively associated with colorectal cancer-specific mortality, and the biologic mechanisms underlying this association are not well understood. 18, 38,39 Other mechanisms for the adverse impact of smoking on colorectal cancer-specific survival may include decreased efficacy of colorectal cancer treatment among smokers. [11][12][13] Although MSI-high tumors generally demonstrate higher survival, 33,34 BRAF mutation status is independently associated with higher risk of mortality, 35 and CIMP-high status in microsatellite-stable tumors is also associated with lower survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, consideration of molecular markers that distinguish these pathways, such as BRAF , is important for better understanding the relationship between lifestyle factors and CRC risk and survival. We have previously identified differences in the relationship between smoking and CRC survival according to these markers (28, 29, 31). Additionally, in a previous paper from the S-CCFR, Coghill et al found that the inverse association between use of non-steroidal anti-inflammatory drugs and survival after CRC diagnosis was restricted to proximal colon cancers, which are more commonly MSI-H and BRAF -mutated than distal CRC (54).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested some heterogeneity in the relationship of lifestyle factors with CRC risk and survival according to these tumor-markers (2631). Thus, consideration of these tumor-markers may provide greater insight into the association between physical activity and CRC survival.…”
Section: Introductionmentioning
confidence: 99%
“…8589 The MPE paradigm, which can encompass all human diseases, 148 is firmly established, 149152 and has gained widespread recognition. 121, 153176 …”
Section: The Genesis Of the “Etiologic Field Effect”mentioning
confidence: 99%